The Effect of Financial Constraints on Relationship between Financial Reporting Quality and Investment Inefficiency - Tariverdi, Yadollah; Keivanfar, Mokhtar (International Journal of Economics and Financial Issues, 2017)
Today, any research about the influence of accounting information in great range of stock holder decisions makers in companies leads to the better understanding of the method and role of information and its better disclosure. Current work was conducted aiming at investigating role of financial constrains in relationship between financial reporting quality and investment inefficiency. Research statistical population includes companies listed in Tehran Stock Exchange during 2008–2013. 112 companies were considered as statistical sample considering predetermined criteria. Data in RahavardNovin Software were used for data collection. Also, financial statements of the companies listed in Tehran Stock Exchange were used. Multivariate regression model, the fixed effects model and generalized least squares estimation method were used for data analysis using Eviews software. In this regression model, variables of growth, size, asset return, cash and objective assets were entered into analysis as control variables. Analysis results show that financial constraints increase opposite effect of financial reporting quality on investment inefficiency. Keywords: Financial Constraints, Financial Reporting Quality, Investment Inefficiency JEL Classifications: E44, G32